Transformasi digital museum seni rupa berbasis 3D virtual tour interaktif dengan Unity - Astuti, Yuli; Fatimah, Tsania Alfina Nur; Fakhruddin, Rangga Romzi (Journal of Information System and Application Development, 2024)
Affandi Museum, located on the banks of the Gajah Wong River at Jalan Laksda Adisucipto No. 167, Yogyakarta, occupies a strategic location that is easily accessible to both domestic and international tourists. However, the museum currently lacks a virtual version for remote visits. To remain relevant and accessible to the digital generation, this research aims to transform Affandi Museum into a 3D Virtual Tour and develop its interactivity using the prototype method. This approach allows for rapid and iterative development, focusing on interactive elements such as navigation, pop-up information, and audio guides, using the Unity platform. Usability testing involves various users to ensure an intuitive interface and optimal experience, resulting in highly valued aspects such as ease of navigation, visual quality, and interactively presented information, with an average rating of 4.7/5. This digital transformation enables Affandi Museum to reach a wider audience and strengthen its position as a center of cultural and art education.